2007
DOI: 10.1029/2007pa001427
|View full text |Cite
|
Sign up to set email alerts
|

An 8‐century tropical Atlantic SST record from the Cariaco Basin: Baseline variability, twentieth‐century warming, and Atlantic hurricane frequency

Abstract: [1] We present the first direct comparison and calibration of a downcore foraminiferal Mg/Ca record to historical instrumental sea surface temperature (SST). Mg/Ca measured on the planktic foraminifer Globigerina bulloides from a Cariaco Basin sediment core strongly correlate with spring (March-May) instrumental SSTs between A.D. 1870 and 1990. A Mg/Ca SST equation is derived and a paleo-SST record is presented spanning the last 8 centuries, an interval that includes the end of the Medieval Warm Period and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 64 publications
8
120
0
1
Order By: Relevance
“…A combination of proxy records suggests that the states of these climate factors converged during the Little Ice Age, and the MM in particular, to create a drastically unfavorable environment for CTC development. The distinct reduction in CTC activity during the MM can be attributed to cool absolute SSTs in the Caribbean (34,35) and in the main development region (36): warmer ocean waters provide more thermal and kinetic energy and thus increase the potential for a greater number of severe storms (31) (Fig. 3E).…”
Section: Significancementioning
confidence: 99%
“…A combination of proxy records suggests that the states of these climate factors converged during the Little Ice Age, and the MM in particular, to create a drastically unfavorable environment for CTC development. The distinct reduction in CTC activity during the MM can be attributed to cool absolute SSTs in the Caribbean (34,35) and in the main development region (36): warmer ocean waters provide more thermal and kinetic energy and thus increase the potential for a greater number of severe storms (31) (Fig. 3E).…”
Section: Significancementioning
confidence: 99%
“…Because of high sedimentation rates, coastal records can often be examined at subdecadal or even shorter (annual or seasonal) time scales Rabalais et al, 1996). For example, Black et al (2007) presented an eight-century record of water temperature (based on Mg/Ca ratios and oxygen isotopes) for the Cariaco Basin with a resolution of 1 to 1.5 years. However, because of sample size limitations, there are few proxy studies at these very fine resolutions.…”
Section: Historical Reconstructions As Part Of Palaeoceanographymentioning
confidence: 99%
“…The proposed Cause C mechanism must necessarily include coupling with the multidecadal-to centennial-scale variations of the Atlantic Intertropical Convergence Zone, as noted in several proxy archives Poore et al, 2004;Peterson and Haug, 2006;Black et al, 2007) and in climate modeling experiments (Vellinga and Wu, 2004;Chiang and Bitz, 2005;Zhang and Delworth, 2005). In general, these studies have highlighted a robust shift of the ITCZ southward during North Atlantic cooling and slower MOC/THC and a northward ITCZ shift during the opposite phase of stronger MOC/THC and warmer North AtlanticArctic conditions.…”
Section: Additional Mechanistic Explanation For Interrelated Causes Amentioning
confidence: 99%
“…The theory of Nilsson, Walin and colleagues viewed the slow upwelling of dense water overall in the low latitudes and the Southern Ocean (see also Visbeck, 2007;Toggweiler and Russell, 2008), rather than high-latitude production and sinking of dense water as the rate-limiting branch of THC. 9 The Nilsson et al theory showed, with a reasonable model of interval wave mixing, that the vertical diffusivity would increase with decreasing surface equator-to-pole density contrast, and that would deepen the thermocline and, in turn, lead to a stronger THC.The proposed Cause C mechanism must necessarily include coupling with the multidecadal-to centennial-scale variations of the Atlantic Intertropical Convergence Zone, as noted in several proxy archives Poore et al, 2004;Peterson and Haug, 2006;Black et al, 2007) and in climate modeling experiments (Vellinga and Wu, 2004;Chiang and Bitz, 2005;Zhang and Delworth, 2005). In general, these studies have highlighted a robust shift of the ITCZ southward during North Atlantic cooling and slower MOC/THC and a northward ITCZ shift during the opposite phase of stronger MOC/THC and warmer North AtlanticArctic conditions.…”
mentioning
confidence: 99%